1999
DOI: 10.1089/cpb.1999.2.69
|View full text |Cite
|
Sign up to set email alerts
|

VREPAR Projects: The Use of Virtual Environments in Psycho-Neuro-Physiological Assessment and Rehabilitation

Abstract: Due, in large part, to the significant advances in PC hardware that have been made over the last 3 years, PC-based virtual environments are approaching reality. Virtual Reality Environments for Psychoneurophysiological Assessment and Rehabilitation (VREPAR) are two European Community funded projects (Telematics for health-HC 1053/HC 1055, http:// www.psicologia.net) that are trying to develop a PC-based virtual reality system (PC-VRS) for the medical market that can be marketed at a price that is accessible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The use of virtual reality encourages a higher number of exercise repetitions. 13,14 It is also described as promoting motor learning through immediate feedback about performed tasks 15 that are related to real-life activities 16,17 such as navigation 18 and road crossing. 19,20 Previous systematic reviews have reported a moderate advantage obtained from VRBR on body functions of the upper limb 21,22 and lower limb, 23 and on activities (especially those related to the lower limb 22,24,25 ) when compared to standard rehabilitation in people with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual reality encourages a higher number of exercise repetitions. 13,14 It is also described as promoting motor learning through immediate feedback about performed tasks 15 that are related to real-life activities 16,17 such as navigation 18 and road crossing. 19,20 Previous systematic reviews have reported a moderate advantage obtained from VRBR on body functions of the upper limb 21,22 and lower limb, 23 and on activities (especially those related to the lower limb 22,24,25 ) when compared to standard rehabilitation in people with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that by bringing together this community of experts, further stimulation of interest from granting agencies will be accelerated. Information on advances in VR technology must be made available to the health care community in a format that is easy-to-understand and invites participation [102]. Future potential applications of VR are really only limited by the imaginations of talented individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that by bringing together this community of experts, further stimulation of interest from granting agencies will be accelerated. Information on advances in VR technology must be made available to the health care community in a format that is easy-to-understand and invites participation [66]. Future potential applications of VR are really only limited by the imaginations of talented individuals.…”
Section: Discussionmentioning
confidence: 99%